Ampullary and Periampullary Tumors: Translational Efforts to Meet a Challenge in Diagnosis and Treatment - Kang, Soonmo Peter; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Ampullary adenocarcinoma is a rare diagnosis and often managed as carcinomas of pancreatobiliary origin. However, there is accumulating evidence unveiling attributes of ampullary carcinomas that are distinct from that of pancreas or biliary cancers. Growing translational efforts in understanding this rare disease are exemplified by Abstracts #161 and #204 presented at the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium. Image: College of Physicians and Surgeons entrance. New York, NY, USA. (Wikimedia Commons by Beyond My Ken)